A framework for capturing the hidden stakeholder system. Issue 3 (23rd October 2012) - Wood, John; Sarkani, Shahram; Mazzuchi, Thomas; Eveleigh, Timothy
Abstract As programs rise in intricacy and scope, the number of stakeholders involved also increases, often driving an exponential growth in program complexity. This complexity is caused by the <![CDATA[n^*(n - 1)/2]]> <inline-graphic xlink:href="ark:/27927/pgg2bg73kb5" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> stakeholder relationships which form an underlying system that influences all aspects of the program. Understanding, managing, and leveraging this stakeholder system will greatly increase a program's probability of success. This paper provides a framework for capturing this stakeholder system in a series of architectural views. These architectural products document the program's stakeholder concerns and also illustrate how those stakeholders interrelate over the system's lifecycle. The ultimate objective for the framework and use of the resulting products is to allow for right‐sized stakeholder involvement, promote effective use of resources, and increase the probability of overall program success with the assurance of lasting stakeholder commitment. Additionally, this unique insertion of Stakeholder Analysis and Social Network Analysis into an Architecture Framework fulfills an original intent of Architecture Framework, capturing the entire sociotechnical enterprise system. ©2012 Wiley Periodicals, Inc. Syst Eng 16